The Tension of Religious-Traditions and the Ideas of Women's Liberation in Dreams of Trespass’ Novel by Fatima Mernisi - Asmarani, Dini; Monica, Sarah; D. Ratri, Sari (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT This article aims to analyze the literary work entitled